The Interaction between Here and Over There in Manuel Pereira Valcárcel’s Work - Curros Ferro, María (Madrygal. Revista de Estudios Gallegos, 2015)
Manuel Pereira Valcárcel’s work is a diary which reflects his first journey from his home town of Ouzande to Madrid. His intimist poetry reveals his innermost character. His own personal development became the author’s main priority as well as trying to avoid being consumed living in such a large city. The author’s personal improvement crosses frontiers and he loses his youth in the process.
Keywords: Manuel Pereira; Galician poetry; time; memories; journeys